2014
DOI: 10.1128/genomea.01222-14
|View full text |Cite|
|
Sign up to set email alerts
|

Draft Genome Sequence of Escherichia coli Strain VKPM B-10182, Producing the Enzyme for Synthesis of Cephalosporin Acids

Abstract: Escherichia coli strain VKPM B-10182, obtained by chemical mutagenesis from E. coli strain ATCC 9637, produces cephalosporin acid synthetase employed in the synthesis of β-lactam antibiotics, such as cefazolin. The draft genome sequence of strain VKPM B-10182 revealed 32 indels and 1,780 point mutations that might account for the improvement in antibiotic synthesis that we observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It turned out that, in HY strains, the target BGCs are upregulated tens to hundreds of times compared to the original natural isolates [42,43]. Moreover, BGC duplications were observed in some HY strains, whereas no increase in gene dosage occurred in others [42,156,[335][336][337][338][339]. It has been shown that target production does not have a linear correlation with the BGC copy number [340], suggesting that some other modification is also important [88].…”
Section: Key Molecular Events Leading To High-yield Production Of Sec...mentioning
confidence: 99%
“…It turned out that, in HY strains, the target BGCs are upregulated tens to hundreds of times compared to the original natural isolates [42,43]. Moreover, BGC duplications were observed in some HY strains, whereas no increase in gene dosage occurred in others [42,156,[335][336][337][338][339]. It has been shown that target production does not have a linear correlation with the BGC copy number [340], suggesting that some other modification is also important [88].…”
Section: Key Molecular Events Leading To High-yield Production Of Sec...mentioning
confidence: 99%